2014
DOI: 10.1007/s10029-014-1295-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after randomizing prolene hernia system, mesh plug repair and lichtenstein for inguinal hernia repair

Abstract: Long-term outcome after randomizing PHS, MPR and L showed no clinically relevant differences in chronic pain and its consequences. Although chronic pain is diminishing over time it remains a serious complication and has sometimes an onset long after the inguinal repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 15 publications
7
21
0
1
Order By: Relevance
“…However, among these studies, 33 different validated instruments were identified (tables 4, 5, 6) [11,13,14,17,19,21,26,28,29,32,36,38,41,43,45,47,48,51,53,56,57,58,59,60,61,62,63,64,65,79,90]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, among these studies, 33 different validated instruments were identified (tables 4, 5, 6) [11,13,14,17,19,21,26,28,29,32,36,38,41,43,45,47,48,51,53,56,57,58,59,60,61,62,63,64,65,79,90]. …”
Section: Resultsmentioning
confidence: 99%
“…In the other 49 studies (61%), a total of 22 different definitions of CPIP were identified. Almost half (n = 23) of these studies applied the definition provided by the IASP, which is ‘chronic pain is pain that persists beyond three months post-operatively' [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. The remaining half (n = 26) used multiple definitions of CPIP, which can be categorized and summarized as follows.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations